Dealing with a common research agenda between the EU and Mediterranean Partner Countries. A methodological approach - Noetzel R.; Morini C.; El-Zoheiry A.H. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
This paper outlines a methodology developed and adopted in the framework of MIRA project thematic workshops, as well as the process of setting regional research priorities implemented through a multidisciplinary and participatory approach. Furthermore, an overview of the key findings and research topics of mutual interest for developing a common EU-MED research agenda, and of the experiences and lessons learnt is presented.